Aiman, a graduate with disabilities, secures UMPSA Degree - Nor Salwana, Mohammad Idris (UMPSA, 2023)
KUANTAN, 21 October 2023 – Self-limitations did not hinder a graduate with disabilities (OKU) from holding a degree at the 18th Convocation Ceremony of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) held at the UMPSA Sports Complex in Gambang recently.